2017
DOI: 10.1002/eji.201646570
|View full text |Cite
|
Sign up to set email alerts
|

“Inflamm‐aging” influences immune cell survival factors in human bone marrow

Abstract: The bone marrow (BM) plays a key role in the long‐term maintenance of immunological memory. However, the impact of aging on the production of survival factors for effector/memory T cells and plasma cells in the human BM has not been studied. We now show that the expression of molecules involved in the maintenance of immunological memory in the human BM changes with age. While IL‐15, which protects potentially harmful CD8+CD28− senescent T cells, increases, IL‐7 decreases. IL‐6, which may synergize with IL‐15, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 55 publications
5
95
3
1
Order By: Relevance
“…Thus, although the responsiveness to IL‐7, IL‐6, and IL‐2 was quite low, DN cells may still respond well to IL‐15. The expression of IL‐15 increases in the BM in the elderly . We now observed increased levels of DN CD8 + T cells in the BM in old age, suggesting that IL‐15 may contribute to the survival of this subset.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, although the responsiveness to IL‐7, IL‐6, and IL‐2 was quite low, DN cells may still respond well to IL‐15. The expression of IL‐15 increases in the BM in the elderly . We now observed increased levels of DN CD8 + T cells in the BM in old age, suggesting that IL‐15 may contribute to the survival of this subset.…”
Section: Discussionmentioning
confidence: 52%
“…We demonstrated that, in the human BM, the production of IL-15 and the numbers of effector/memory CD8 + T cells increased with age and a link with inflammation was found (12, 32). However, it is still unclear how CMV positivity affects CD8 + T cells in the BM, particularly, highly differentiated effector cells.…”
Section: Discussionmentioning
confidence: 81%
“…In regenerating tissue of acute inflammation, this may help to get rid of tissue‐resident plasma cells of the acute immune reaction, ie, terminate the peak response. It also may contribute to the age‐dependent decay of humoral memory 49, 50…”
Section: Conditional Survival Of Memory Plasma Cells—the Memory Nichementioning
confidence: 99%
“…It also may contribute to the age-dependent decay of humoral memory. 49,50 Although stromal cells are a key element of the memory plasma cell niche, they are not the only element. Stromal cells do not express BAFF or APRIL themselves, and it is obvious that those ligands of BCMA, the second essential survival signal for memory plasma cells, have to be provided by other cells, which we have termed "accessory" cells of the niche.…”
Section: Conditional Survival Of Memory Pl a S Ma Cell S-the Memorymentioning
confidence: 99%